2020
DOI: 10.30534/ijeter/2020/38862020
|View full text |Cite
|
Sign up to set email alerts
|

ASD Children Gait Classification Based On Principal Component Analysis and Linear Discriminant Analysis

Abstract: The aim of this study is to explore the potential of the markerless-based gait features using both unsupervised and supervised algorithms namely the Principal Component Analysis (PCA) and Linear Discriminant Analysis (LDA) as feature extraction techniques. Firstly, a depth camera that created the three-dimensional (3D) skeleton image of the subject upon detection of movements by the motion sensor is used as data acquisition device in acquiring the walking gait of 30 TD and 23 ASD group. Next, the extracted gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…For example, Vilensky et al [19] used two high-speed cameras, with one camera was placed perpendicularly with the walking track while the other camera was facing the track to measure gait disturbance between the normal and autistic children at the hip, knee, and ankle joints. Meanwhile, Zakaria et al [20] performed ASD gait classification based on the calculated distance between joints captured by the depth camera.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Vilensky et al [19] used two high-speed cameras, with one camera was placed perpendicularly with the walking track while the other camera was facing the track to measure gait disturbance between the normal and autistic children at the hip, knee, and ankle joints. Meanwhile, Zakaria et al [20] performed ASD gait classification based on the calculated distance between joints captured by the depth camera.…”
Section: Related Workmentioning
confidence: 99%
“…To further understand gait patterns in children with ASD versus neurotypical controls, there has been a recent increase in the number of studies using machine learning (ML) tools for classification based on combinations of kinematic and kinetic features [ 7 , 14 , 15 , 16 , 17 , 18 , 19 ]. Such studies facilitate the identification of discriminatory gait features in ASD versus neurotypical controls, which may lead to the development of automated gait classifiers, optimal treatment plans, improved functionality for children, and reduced health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has investigated the classification of ASD and control gait patterns using temporal-spatial, kinematic, and kinetic features [ 7 , 14 , 15 , 16 , 17 , 18 , 19 ]. Ilias et al, (2006) observed that the fusion of all these features resulted in a classification accuracy of 95.80% (sensitivity 100%, specificity 85.00%) using a support vector machine (SVM) classifier [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several statistical studies were carried out to prove the sensitivity of features in measuring the expected pathologies. Zakaria et al [7] classified Autism Spectrum Disorder (ASD) children's gait from normal gait. Gait features were the absolute or relative Cartesian coordinates of 20 joints of the subject measured by a depth camera.…”
Section: Introductionmentioning
confidence: 99%